Soil Contamination And Its Effects On Beans (Phaseolus Vulgaris L.) Growth Affected By Organic Matter, And Associated With Glomus Intrarradices - Gardezi, Abdul Khalil; Marquez-Berber, Sergio Roberto; Martinez-Menes, Mario; Flores-Magdaleno, Hector; Escalona-Maurice, Miguel Jorge; Larque-Saavedra, Mario Ulises; Almaguer-Vargas, Gustavo (European Scientific Journal, ESJ, 2016)
Contamination is a growing problem affecting irrigation water. The objective of this research was to evaluate the effect of two sources of irrigation water, clean one, sewage water, and organic matter on the association with Glomus intrarradices on beans (Phaseolus vulgaris L.). The interpolation of the chemical analysis did not find differences between clean and sewage waters regarding the increase of contaminants in the soil. The contamination of the soil by sewage water did not affect plant growth or yield. It only affected nitrogen fixation. There were highly significant increases (pâ‰¤0.05) in all the variables recorded due to the application of organic matter, and to the inoculation with Glomus intrarradices. The irrigation source of the soils used in this experiment only had a significant effect (pâ‰¤0.05) on pod number and nitrogen fixation. The best growth and grain yield occurred with inoculated plants and supplementary organic matter.